A New Technique of Laplace Variational Iteration Method for Solving Space-Time Fractional Telegraph Equations. (22nd December 2013) - Alawad, Fatima A.; Yousif, Eltayeb A.; Arbab, Arbab I.
Abstract : In this paper, the exact solutions of space-time fractional telegraph equations are given in terms of Mittage-Leffler functions via a combination of Laplace transform and variational iteration method. New techniques are used to overcome the difficulties arising in identifying the general Lagrange multiplier. As a special case, the obtained solutions reduce to the solutions of standard telegraph equations of the integer orders.